A tradição oral dos povos Baniwa e Baré na língua Yẽgatu: desafios da educação escolar indígena - Martins, Maria do Rosário Piloto (2022)
The objective of this work is to discuss indigenous school education based on the linguistic and cultural diversity of the peoples of the Upper Rio Negro, in the state of Amazonas. For that, we make a literary reading of oral narratives Baniwa and Baré, two Aruak peoples. The invasion of their lands and the non-indigenous school education promoted by the Salesians and pastors, without the presence of the Brazilian State, created the conditions for the Baniwa of the Upper Rio Negro to be forced to stop using the language of their ethnic identity. At the same time, the presence of Yẽgatu (general Amazonian language), initially as a language of domination in the region, and later as a language of contact between indigenous and non-indigenous people, creates the conditions for it to become the native language of Baré, Baniwa of the lower Içana River and Warekena of the Xié River, three peoples of the Arawak group. The replacement of the traditional languages of these peoples by Yẽgatu explains why the two mythical narratives, one of the Baniwa people, and the other of the Baré people, written by the wise men José Marcelino Cordeiro of the Baniwa people and Senhor Antenor Costa of the Baré people, are in Yẽgatu. The narratives were collected between 2019 and 2020. They show the importance of knowing the thoughts and feelings of the Baniwa people. In the case of this research, it will be based on the collection of these two narratives via voice recording made with the two leaders of the Baniwa and Baré communities, speakers of Yẽgatu. We will analyze the translation processes of oral mythological narratives, seeking to identify the changes in the passage from the oral expression of Baniwa and Baré to the written expression in Yẽgatu. With this research, I hope to expand the understanding of the knowledge transmission systems through the oral language of the Baré and Baniwa peoples.